PowerPoint 2016 (LiveLessons., 2016)
"PowerPoint 2016 LiveLessons shows you how to work in PowerPoint with confidence and ease. You learn how to format text, charts, and tables, as well as the finer points of creating SmartArt graphics and even your own shapes. You learn about tools such as Smart Guides, color eyedroppers, and style galleries that will help you with everyday tasks. Master high-powered skills at your own pace and harness the power or PowerPoint 2016."--Resource description page.